Manifestasi Prinsip Good Governance dalam Pengelolaan Arsip Dinamis Aktif di Kantor Imigrasi Kelas I TPI Yogyakarta - Arif, Raihan Ahmad; Bawono, Sri Kuncoro; Nurkumalawati, Intan (JoEMS (Journal of Education and Management Studies), 2025)
This article discusses the importance of records management as a key element in supporting good governance at the Class I TPI Immigration Office in Yogyakarta. With the advancement of information technology, active dynamic records have become essential for maintaining the speed and accuracy of public services. Proper records management supports transparency, accountability, and effectiveness, which are core principles of good governance. According to Law No. 43 of 2009 on Archiving, active dynamic records not only serve as authentic sources of information but also hold administrative, legal, and historical value for institutions. This paper aims to identify the application of these principles in managing active dynamic records at the Yogyakarta Immigration Office and address various challenges faced, such as limited understanding of the importance of records management and low support from leadership. Through a systematic approach and the use of technology, this study provides insights into strategies to maximize the role of records as a support tool in public services and to maintain public trust in government institutions.